The Utility Of Anatomy Assessment In Preclinical Undergraduate Medical Curricula: A Scoping Review - Choy Ker Woon; Kah Hui Wong; Aspalilah Alias; Razif Abas; Siti Nurma Hanim Hadie (WILEY, 2025)
Indexed by Scopus